Community Participation and Impact of Tourism Objects on Community Economic Activities in Leang Kassi (Study in Biraeng Village, Minasatene District, Pangkajene Regency and Islands) - Harlinda Ramli; Abd Malik; Ibrahim Abbas (UNM Geographic Journal, 2020)
This study aims to determine: 1) How is the community's participation in tourism development in Leang Kassi 2) What is the form of economic activities carried out by the community. The population in this study were all residents of Biraeng Village, amounting to 6778 people. The sample in this study amounted to 99 people. This research is a quantitative descriptive study. Data collection techniques include observation, questionnaires and documentation. Data analysis was performed by descriptive analysis and multiple regression equations. Based on the research results, the level of public knowledge of tourist objects is in the very agree category, namely 54.56%, for people's attitudes towards tourist objects is in the strongly agree category, namely 49%. Public participation in the economic activity category strongly agrees, namely 63%, economic activities in tourist objects are in the strongly agree category, namely 23.98%. The test results of the influence of tourism objects on economic activities, community participation on economic activities together are 16.90% and 83.10% are influenced by other factors outside the tourist attraction and participation variable factors.